Impact of Prosthesis Length on Tympanic Membrane's and Annular Ligament's Stiffness and the Resulting Middle Ear Sound Transmission. Issue 9 (October 2016) - Neudert, Marcus; Bornitz, Matthias; Lasurashvili, Nikoloz; Schmidt, Uwe; Beleites, Thomas; Zahnert, Thomas
Abstract : Supplemental Digital Content is available in the text Abstract : Hypothesis: Prosthesis' length creates tension in ossicular reconstructions, which directly effects the middle ear sound transmission. Background: Relatively long prostheses are often used to stabilize the middle ear reconstruction to prevent dislocation. Thereby, tension on the flexible components such as the tympanic membrane (TM) and the annular ligament (AL) is increased. Only little is known on the amount of displacement-related stiffening of the TM and AL, as well as the consecutive reduction in middle ear transfer function (METF). Methods: An expandable total ossicular replacement prosthesis was tensionfree inserted in nine cadaveric temporal bones between the malleus handle and the stapes footplate. Upon heat activation the prosthesis was lengthened, thus inducing tension on the reconstruction. The METF was assessed before and after elongation. TM's and AL's stiffness were determined by measuring their force–displacement characteristics. Results: Upon activation the prostheses were elongated between 50 and 200 μm. A frequency-dependent METF reduction was measured with a decrease of 5 to 25 dB below 1.0 kHz. At frequencies >2.0 kHz the reduction was less prominent or the METF showed even an improvement of up to 10 dB. TM's stiffness remained constant during the elongation-induced displacement, whereas the AL's stiffness increased. The METF reduction below 1.0 kHz correlated with the increasing AL's stiffness. Conclusion: Tension has a significant impact on the METF after middle ear reconstruction. As little tension as possible should be used to enable best sound transmission. Stabilization of prosthesis should be achieved with dislocation devices to ensure secure coupling to the ossicular remnants without creating additional tension.